Acute ischaemia after subarachnoid haemorrhage, relationship with early brain injury and impact on outcome: a prospective quantitative MRI study. Issue 1 (8th April 2014) - Frontera, Jennifer A; Ahmed, Wamda; Zach, Victor; Jovine, Maximo; Tanenbaum, Lawrence; Sehba, Fatima; Patel, Aman; Bederson, Joshua B; Gordon, Errol
Abstract : Objective: To determine if ischaemia is a mechanism of early brain injury at the time of aneurysm rupture in subarachnoid haemorrhage (SAH) and if early MRI ischaemia correlates with admission clinical status and functional outcome. Methods: In a prospective, hypothesis-driven study patients with SAH underwent MRI within 0–3 days of ictus (prior to vasospasm) and a repeat MRI (median 7 days). The volume and number of diffusion weighted imaging (DWI) positive/apparent diffusion coefficient (ADC) dark lesions on acute MRI were quantitatively assessed. The association of early ischaemia, admission clinical status, risk factors and 3-month outcome were analysed. Results: In 61 patients with SAH, 131 MRI were performed. Early ischaemia occurred in 40 (66%) with a mean DWI/ADC volume 8.6 mL (0–198 mL) and lesion number 4.3 (0–25). The presence of any early DWI/ADC lesion and increasing lesion volume were associated with worse Hunt-Hess grade, Glasgow Coma Scale score and Acute Physiology and Chronic Health Evaluation II physiological subscores (all p<0.05). Early DWI/ADC lesions significantly predicted increased number and volume of infarcts on follow-up MRI (p<0.005). At 3 months, early DWI/ADC lesion volume was significantly associated with higher rates of death (21% vs 3%, p=0.031), death/severe disability (modified Rankin Scale 4–6; 53% vs 15%, p=0.003) and worse Barthel Index (70 vs 100, p=0.004). After adjusting for age, Hunt-Hess grade and aneurysm size, early infarct volume correlated with death/severe disability (adjusted OR 1.7, 95% CI 1.0 to 3.2, p=0.066). Conclusions: Early ischaemia is related to poor acute neurological status after SAH and predicts future ischaemia and worse functional outcomes. Treatments addressing acute ischaemia should be evaluated for their effect on outcome.